DEVELOPMENT OF MODEL TO PROMOTE ACCESS TO VACCINE AGAINST CORONAVIRUS 2019 INFECTION IN RISK GROUP, PHAYAO PROVINCE - พิสิษฐ์กุล, ฉัตรศิริ; เมืองชื่น, สมภพ; ธรรมชาวนา, วรัญญา (Primary Health Care Journal (Northeastern Edition), 2025)
This research and development study aimed to design and evaluate a model for enhancing access to COVID-19 vaccination among high-risk populations in Phayao Province, Thailand. The study was conducted in three phases: (1) situation analysis and initial model development, (2) pilot implementation and model refinement, and (3) full-scale implementation and outcome evaluation. The research employed Kemmis and McTaggart’s PAOR cycle, comprising four iterative steps: Planning, Action, Observation, and Reflection. A mixed-methods approach was applied between November 2023 and July 2024. Qualitative data were collected through focus group discussions, in-depth interviews, and community participatory activities involving 75 stakeholders. Quantitative data were obtained from 400 individuals in the high-risk group-defined as adults aged 60 years and older and individuals with one of seven chronic conditions-using structured questionnaires. Descriptive statistics were used for quantitative analysis, while qualitative data were analyzed using content analysis. The developed model for improving vaccine accessibility included: (1) multisectoral collaboration among community stakeholders, (2) targeted communication and participatory data-sharing for identifying and evaluating priority groups, (3) capacity-building for community leaders and village health volunteers (VHVs) to enhance health communication and motivation, (4) outreach through household surveys and home visits to unvaccinated individuals, and (5) proactive vaccination services delivered at subdistrict health centers and home settings for the home-bound or bedridden. Implementation of the model resulted in 225 out of 400 high-risk individuals receiving a COVID-19 booster dose, reflecting a 56.25% increase in vaccination coverage. These findings highlight the effectiveness of a community-engaged, multi-component strategy in improving vaccine access among vulnerable populations.